The Deep Determinants at More Subtle Stages of Development: The Example of the Middle-Income Trap Phenomenon - Linda Glawe; Helmut Wagner (University of Hagen, Center for East Asia Macro-economic Studies (CEAMeS), 2017)
The so-called 'deep determinants' of economic growth and development (namely, geography, institutions, and integration) have been found to be decisive for the break out of stagnation and for explaining cross-country income differences by many empirical studies. However, so far, very little has been done to examine to which extent they are also crucial at more subtle stages of economic development. Our paper aims to close this gap by focusing on the phenomenon of the middle-income trap (MIT) which has reached increasing attention in the last 15 years. In particular, we test whether the results of the empirical studies conducted by Acemoglu et al. (2001), Rodrik et al. (2004), and Easterly and Levine (2016) also remain valid when analyzing the MIT. We are the first to analyze the relationship between the deep determinants and the MIT, especially regarding the causal effect of institutional quality on the probability of experiencing a growth slowdown at the middle-income range. Our analysis reveals that while, in general, the deep determinants also seem to play an important role for the middle-income transition (and the question of whether a country falls into an MIT), some differences compared to the results of the standard literature become apparent.
urn:nbn:de:hbz:708-dh9586
Keywords: O10; O11; O43; O57; 330; deep determinants of growth; economic development; economic growth; middle-income trap; geography; institutions; openness